2009
DOI: 10.1590/s0034-71672009000100015
|View full text |Cite
|
Sign up to set email alerts
|

Religião e espiritualidade: experiência de famílias de crianças com Insuficiência Renal Crônica

Abstract: It is important for nurses to understand the family's religious and spirituality in the disease process, with a view to their work in health promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
34

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 24 publications
0
29
0
34
Order By: Relevance
“…In 2009, Paula et al 37 published a qualitative study assessing four families of children on peritoneal dialysis and reported manifestations of spirituality and religiosity. The mothers claimed that "God is the hope for cure of chronic disease" and "God can protect children from clinical complications".…”
Section: Methodsmentioning
confidence: 99%
“…In 2009, Paula et al 37 published a qualitative study assessing four families of children on peritoneal dialysis and reported manifestations of spirituality and religiosity. The mothers claimed that "God is the hope for cure of chronic disease" and "God can protect children from clinical complications".…”
Section: Methodsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15] In 20052, [16][17][18][19] 24 Except one, 37 all papers included in the review used the genogram and ecomap as complementary tools for research data collection. One paper was identified in which the contribution of the genogram and the ecomap was explored in undergraduate nursing education and in childcare.…”
Section: Resultsmentioning
confidence: 99%
“…Papers were identified with "families" of: elderly people; 10,12,24,32 pregnant women with human papillomavirus; 23,27 women with human papillomavirus, in the form of a case study; 11 adults with arterial hypertension and diabetes mellitus; 8 nursing faculty members; 29 children who were victims of violence; 31 children with cancer 2 and chronic kidney failure; [9][10][11][12][13][14][15][16] patients with mental disorders; 3,14,28 users registered in the Family Health Program; 19 adults with chronic kidney failure; 13 hospitalized patients; 20 adolescent parents; 7 people living in rural areas 36 and, in one study, to understand the family context in the health-disease process. 25 "Individually", these instruments were used: with mental health service users; 15 with mothers of premature children; 6,21 mothers of pre-adolescents; 17 patients with traumatic spinal cord injury; 18 children in early childhood; 26 children with nephrotic syndrome; 30 stoma patients; 22 elderly people [33][34] and young victims of violence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations